Guillain-Barré syndrome following Zika virus infection is associated with a diverse spectrum of peripheral nerve reactive antibodies - Davies, AJ; Lleixà, C; Siles, AM; Gourlay, D; Berridge, G; Dejnirattisai, W; Ramírez-Santana, C; Anaya, J-M; Falconar, AK; Romero-Vivas, CM; Osorio, L; Parra, B; et al. (Lippincott, Williams & Wilkins, 2022)
Background and Objectives Recent outbreaks of Zika virus (ZIKV) in South and Central America have highlighted significant neurological side effects. Concurrence with the inflammatory neuropathy Guillain-Barré syndrome (GBS) is observed in 1:4000 ZIKV cases. Whether the neurological symptoms of ZIKV infection are immune-mediated is unclear. We employed rodent and human live cellular models to screen for anti-peripheral nerve reactive IgG and IgM autoantibodies in sera of ZIKV patients with and without GBS. Methods In this study, 52 ZIKV-GBS patients were compared with 134 ZIKV-infected patients without GBS, and 91 non-ZIKV controls. Positive sera were taken forward for target identification by immunoprecipitation and mass spectrometry, and candidate antigens validated by ELISA and cell-based assays. Autoantibody reactions against glycolipid antigens were also screened on an array. Results Overall, IgG antibody reactivities to rat Schwann cells (SCs) (6.5%) and myelinated co-cultures (9.6%) were significantly higher, albeit infrequent, in the ZIKV-GBS group compared to all controls. IgM antibody immunoreactivity to dorsal root ganglia (DRG) neurones (32.3%) and SCs (19.4%) was more frequently observed in the ZIKV-GBS group compared to other controls, while IgM reactivity to co-cultures was as common in ZIKV and non-ZIKV sera. Strong axonal-binding ZIKV-GBS serum IgG antibodies from one patient were confirmed to react with neurofascin 155 and 186. Serum from a ZIKV non-GBS patient displayed strong myelin-binding and putative anti-lipid antigen reaction characteristics. There was however no significant association of ZIKV-GBS with any known anti-glycolipid antibodies. Conclusion Autoantibody responses in ZIKV-GBS target heterogeneous peripheral nerve antigens suggesting heterogeneity of the humoral immune response despite a common prodromal infection.